The Relationship between Family Support and Entrepreneurial Interest of PKW Sewing Fashion Graduates in LKP Kasih Bunda Pesisir Selatan - Susanti, Nengsi; Sunarti, Vevi (Universitas Negeri Padang, 2024)
This research is motivated by the low interest in entrepreneurship for PKW graduates sewing dressmaking at LKP Kasih Bunda Pesisir Selatan. One reason is the low family support. The purpose of this study was to describe family support and interest in entrepreneurship for PKW graduates sewing dresses at LKP Kasih Bunda Pesisir Selatan and to see the relationship between family support and interest in entrepreneurship for PKW graduates sewing dresses at LKP Kasih Bunda Pesisir Selatan. This study uses a quantitative approach to the type of correlational research. The population of this study were 50 PKW graduates sewing fashion at LKP Kasih Bunda in 2021. The sample of this study consisted of 35 people using cluster random sampling technique. Data collection techniques and tools using a questionnaire. Data analysis techniques use percentage and product moments. The results of this study indicate that (1) the support provided by the family is low; (2) the interest in entrepreneurship for PKW graduates in sewing fashion at LKP Kasih Bunda Pesisir Selatan is low; and (3) there is a significant relationship between family support and the interest in entrepreneurship for PKW graduates sewing fashion at LKP Kasih Bunda Pesisir Selatan.